Evaluation of ITO/TiO2/Co3O4 as a non-enzymatic heterojunction electrode to glucose electrooxidation - Neto, Nilton Francelosi Azevedo [UNESP]; de Jesus Pereira, André Luiz; Leite, Douglas Marcel Gonçalves; da Silva, José Humberto Dias [UNESP]; da Silva Pelissari, Marcelo Rodrigues [UNESP] (Springer Nature, 2021)
Electroactive Co3O4 films were deposited by reactive magnetron sputtering (RMS) onto an assembly composed of a thin TiO2 layer over a commercial indium-doped tin oxide (ITO) conductor electrode, forming an ITO/TiO2/Co3O4 electrocatalytic platform. The platform was tested as a non-enzymatic device for glucose electrooxidation. The characterization of the electroactive TiO2/Co3O4 heterojunction was carried out by x-ray diffraction (XRD), Raman spectroscopy, field-emission scanning electron microscope (FE-SEM), and energy dispersive spectroscopy (EDS) techniques. It was shown that the Co3O4 top layer is homogeneous and free from undesirable secondary phases. The electrochemical measurements, characterization and performance, were carried out by cyclic voltammetry (CV), chronoamperometry, and electrochemical impedance spectroscopy (EIS). The cyclic voltammogram shows the linear dependence between the anodic and cathodic current peak of the redox process at the electrode surface, showing the electrochemical activity of the Co3+/Co4+ redox pair, as well as good reversibility and efficiency of charge transfer. From the chronoamperometric curves, two electrochemical parameters were estimated, the diffusion coefficient (D) and catalytic rate constant (kobs) of glucose with the values of 1.2 × 10−6 cm2 s−1 and 2.8 × 106 cm3 mol−1 s−1, respectively. The ITO/TiO2/Co3O4 heterojunction electrode showed an acceptable linear range from 10 to 1000 μM glucose concentration with a molar sensitivity (S) of 30.0 μA cm−2 mM−1 and a detection limit (LOD) of 1.42 μM (S/N = 3). These electrochemical results show the higher electroactivity of TiO2/Co3O4 heterojunction electrode than that of bare Co3O4 electrode and other literature results.
Keywords: Glucose electrooxidation; Heterojunction; ITO/TIO2/Co3O4; Non-enzymatic; Reactive magnetron sputtering (RMS)